TEACHER'S SPEECH MODIFICATIONS IN AN EFL CLASSROOM - Hikmat Abdul Aziz, - (2011)
This study investigates teacher's speech modification in elementary school students. The data were analyzed qualitatively using Moritoshi's (n.d.) taxonomy of speech modifications adapted from Chaudron (1988). The domain of teacher's talk modified were including phonology by modified pronunciation, timing by modified pauses, lexis by preferred use basic and high frequency vocabulary, syntax by modified grammaticality, and discourse by modified framing moves and self repetition. In addition, there was also strategy that was not included in taxonomy speech of modifications but applied by the teacher, code switching.